Financial Performance of Initial Public Offerings: Exploratory Study - Ait Jillali, Sanae; Belkasseh, Mohammed (Archives of Business Research, 2022)
The subject of prowess and relevance constantly represents an apprehension of the leaders which alerts the presence of the firm in its market notwithstanding their definitions and complicated measures emanating from the determination of the performance. The latter, as being a kaleidoscopic and multidimensional construct, can never illustrate a consensus of the authors. The present study allows us to constitute a frame of reference to prepare the ground of an investigation concerning financial performance before and after Initial Public Offerings (IPOs) in companies listed on the Casablanca Stock Exchange in Morocco. The object of this paper is to offer a literature review that highlights the explanatory factors of an IPO decision and its impact on financial performance. Notably through theoretical foundations which underlie the decision to go public and its effect on performance, namely: the theory of the agency and the timing of the market theory (founded on the assumption of earnings management). As well, based on international empirical studies that demonstrated the behavior of listed companies (regardless of their structure or their line of business) in terms of performance in a period pre- and post-listing. By using different aggregates and performance indicators, the studies’ findings proved the phenomenon of higher financial performance that improves faster than normal during the year before but diminishes after the going public event in the long run. This article brings a more holistic and integrated view of the relationship between IPO and performance, as well as avenues for future research are offered in the conclusion.